2020
DOI: 10.1111/jcmm.15288
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide inhibits angiotensin II‐induced NADPH oxidase‐dependent ROS via the Src/STAT3 signalling pathway

Abstract: We had previously demonstrated that the calcitonin gene‐related peptide (CGRP) suppresses the oxidative stress and vascular smooth muscle cell (VSMC) proliferation induced by vascular injury. A recent study also indicated that CGRP protects against the onset and development of angiotensin II (Ang II)‐induced hypertension, vascular hypertrophy and oxidative stress. However, the mechanism behind the effects of CGRP on Ang II‐induced oxidative stress is unclear. CGRP significantly suppressed the level of reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Indeed, the CGRP has been involved in antioxidant activation, both in vivo and in vitro, other than in nociception [ 18 , 19 , 24 , 25 , 26 ]. In this scenario, we were not able to define which role is played exclusively by the CGRP-signaling blockage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the CGRP has been involved in antioxidant activation, both in vivo and in vitro, other than in nociception [ 18 , 19 , 24 , 25 , 26 ]. In this scenario, we were not able to define which role is played exclusively by the CGRP-signaling blockage.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms of BoNT/A effectiveness in chronic migraine prophylaxis are not clear; however, lower peripheral plasmatic levels of CGRP have been reported after BoNT/A treatment [ 16 ]. However, aside from nociception, CGRP plays a role in oxidative stress, as reported by recent studies [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 96%
“…Orientin inhibits H2O2-induced apoptosis of PC12 cells by inhibiting ROS-mediated Src-MAPK/AKT signal transduction [ 88 ]. Src mediates the activation of STAT3 in vascular smooth muscle cells stimulated by Ang II, which increases ROS production and induces oxidative stress [ 89 ].…”
Section: The Pathophysiological Role Of Sfks In Akimentioning
confidence: 99%
“…Oxidative stress was reported to promote the migration, invasion, and metastasis of NSCLC through the LATS2/YAP signaling pathway in a recent study [ 101 ]. Reactive oxygen species (ROS) are the downstream products of oxidative stress and have been identified to be involved in response to anti-cancer therapies in human NSCLC [ 102 , 103 ]. A previous study by Huang et al reported that the activation of YAP increased the accumulation of ROS by downregulating the antioxidant enzyme GPX2 in human lung squamous cell carcinoma [ 104 ].…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%